Inherent variation in multiple shoe-sole test impressions. (April 2018) - Shor, Yaron; Wiesner, Sarena; Tsach, Tsadok; Gurel, Ron; Yekutieli, Yoram
Highlights: Impressions made by the same shoe, differ to some extent from each other. It is important to create several test impression from each shoe examined. Powder used for impressions might fill in fine scratches and conceal them. Fringes on the sole change position in each impression. The projection of 3D a shoe-sole to a 2D print causes variations. Abstract: Shoeprints left at crime scenes are seldom perfect. Many prints are distorted or contaminated by various materials. Noisy background often contributes to vagueness on the shoeprints as well. Test impressions made from the suspect's shoes in the laboratory are considered a genuine replication of the shoe-sole. This naïve attitude is far from being correct. Consecutive test impressions made in the laboratory under strict similar conditions revealed differences among the exemplars of the same sole. Some of them are minor, but some are major, and can mislead the less experienced practitioners during the comparison process. This article focuses on the inherent within source variability between controlled shoeprints made from the same shoe, as it appears on the RACs. To describe and analyze this variability, repeated test impressions were prepared, and datasets were created. Several RACs were marked on each test impression, using an expert assisting software tool (developed in the authors' lab). The variance in repeated test impressions is demonstrated and possible sources are discussed. This variance should be considered when trying to establish the degree of matching between individual characteristics.